Facile Synthesis of Microporous Carbons from Biomass Waste as High Performance Supports for Dehydrogenation of Formic Acid - Tingting Cao; Jinke Cheng; Jun Ma; Chunliang Yang; Mengqin Yao; Fei Liu; Min Deng; Xiaodan Wang; Yuan Ren (Nanomaterials, 2021)
Formic acid (FA) is found to be a potential candidate for the storage of hydrogen. For dehydrogenation of FA, the supports of our catalysts were acquired by conducting ZnCl2 treatment and carbonation for biomass waste. The texture and surface properties significantly affected the size and dispersion of Pd and its interaction with the support so as to cause the superior catalytic performance of catalysts. Microporous carbon obtained by carbonization of ZnCl2 activated peanut shells (CPS-ZnCl2) possessing surface areas of 629 m2·g−1 and a micropore rate of 73.5%. For ZnCl2 activated melon seed (CMS-ZnCl2), the surface area and micropore rate increased to 1081 m2·g−1 and 80.0%, respectively. In addition, the introduction of ZnCl2 also caused the increase in surface O content and reduced the acidity of the catalyst. The results represented that CMS-ZnCl2 with uniform honeycomb morphology displayed the best properties, and the as-prepared Pd/CMS-ZnCl2 catalyst afforded 100% hydrogen selectivity as well as excellent catalytic activity with an initial high turnover number (TON) value of 28.3 at 30 °C and 100.1 at 60 °C.